STUDENTS’ PERCEPTIONS OF WEBSITE-BASED LEARNING MEDIA: REDEFINING MEANINGFUL SCIENCE EDUCATION IN INDONESIAN ELEMENTARY SCHOOLS - Samih Lestari; Amalia Sapriati; Linda Zakiah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe students’ perceptions of the use of website-based learning media in Natural Science (IPA) instruction at the elementary school level. The research employed a qualitative approach using a case study method involving fifth-grade students at an elementary school in Indonesia. Data were collected through observations, in-depth interviews, and document analysis. The findings indicate that the utilization of website-based learning media has a positive impact on students’ learning processes. The media enhance learning motivation through engaging and interactive features, strengthen conceptual understanding through visual and contextual material presentation, and foster learning independence by allowing students to manage their study time and strategies autonomously. Moreover, the use of website media contributes to improved learning outcomes, the development of digital literacy, and the promotion of social collaboration through online discussions and interactions among students. The successful implementation of this digital media is supported by factors such as technology accessibility, teacher competence in using digital tools, and the alignment of learning materials with the curriculum. Overall, the findings affirm that website-based learning media play a strategic role in creating innovative, meaningful, and 21st-century-oriented science learning experiences